The system's genetics of depression and its somatic and mental comorbidities - Kalinichenko, Liubov; Kornhuber, Johannes; Müller, Christian P. (Translational Neuroscience, 2022)
Depression is a common mood disorder characterised by high comorbidity with other mental and somatic diseases. New studies reveal a shared genetic base for mental core symptoms and somatic comorbidities. Functional analyses showed multiple brain-body pathways involved. This may help considering new therapeutic approaches for depression as a system's disorder.
CRIS-Team WoS Importer:2022-08-05